What factors contribute to hospital variation in obstetric transfusion rates?. Issue 1 (4th August 2014) - Patterson, J. A.; Roberts, C. L.; Isbister, J. P.; Irving, D. O.; Nicholl, M. C.; Morris, J. M.; Ford, J. B.
<x xml:space="preserve">Abstract</x> Background and Objectives To explore variation in red blood cell transfusion rates between hospitals, and the extent to which this can be explained. A secondary objective was to assess whether hospital transfusion rates are associated with maternal morbidity. Materials and Methods Linked hospital discharge and birth data were used to identify births (n = 279 145) in hospitals with at least 10 deliveries per annum between 2008 and 2010 in New South Wales, Australia. To investigate transfusion rates, a series of random‐effects multilevel logistic regression models were fitted, progressively adjusting for maternal, obstetric and hospital factors. Correlations between hospital transfusion and maternal, neonatal morbidity and readmission rates were assessed. Results Overall, the transfusion rate was 1·4% (hospital range 0·6–2·9) across 89 hospitals. Adjusting for maternal casemix reduced the variation between hospitals by 26%. Adjustment for obstetric interventions further reduced variation by 8% and a further 39% after adjustment for hospital type (range 1·1–2·0%). At a hospital level, high transfusion rates were moderately correlated with maternal morbidity (0·59, P = 0·01), but not with low Apgar scores (0·39, P = 0·08), or readmission rates (0·18, P = 0·29). Conclusion Both casemix and practice differences contributed to the variation in transfusion rates between hospitals. The relationship between outcomes and transfusion rates was variable; however, low transfusion rates were not associated with worse outcomes.